PSYCHOLOGICAL WELL-BEING OF CKD PATIENTS AND INFLUENTIAL FACTORS: A CORRELATION STUDY - Djuria, Syafrina Arbaani; Epi Rustiawati (Nursing Sciences Journal, 2025)
Chronic Kidney Disease (CKD) is a major global health problem due to its irreversible nature due to the inability of the kidneys to function optimally in carrying out their regulation. CKD patients can experience psychological problems, requiring spiritual needs and family support that can affect psychological well-being. This study aims to determine the relationship between psychological well-being and influencing factors in CKD patients. This research method used a quantitative research type with a cross-sectional design. The population of this study was all CKD patients treated in the Hemodialysis Room at Dr. Adjidarmo Regional General Hospital with a sample size of 115 people using quota sampling in August 2025. Data analysis used univariate and bivariate using the chi-square test. The results showed a significant relationship between spirituality and psychological well-being (p-value 0.001 <0.05) and no relationship between family support and psychological well-being (p-value 0.08>0.05). High spirituality will have a 3.54 times greater chance of having good psychological well-being compared to low spirituality. In conclusion, nurses need to pay attention to the spiritual aspect of CKD patients in order to improve the psychological well-being of patients by implementing spiritual care for patients.